2014
DOI: 10.1002/jee.20044
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Motivation: A Gateway to Transforming Engineering Education

Abstract: Background Transformative change in higher education requires a continuous interplay between educational research and educational practice. In considering how to engage researchers and practitioners in "cycles of educational practice and research" (Jamieson & Lohmann, 2009), we focus on individuals and what motivates them to create and sustain innovations within the engineering education system.Purpose Through this study, we seek to better understand why faculty do or do not engage in the research-practice cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 38 publications
2
66
0
Order By: Relevance
“…This perspective is also seen in the decisional balance associated with TTM and the decision to make health behavioral changes. As summarized by Matusovich et al 9 , in a review of literature on Expectancy Value Theory and the adoption of teaching practices, all four categories are observed in faculty decisions regarding instructional approaches 10 . This perspective was also seen in Finelli et al's 11 focus group of faculty: expectancy was clustered around knowledge and skills of effective teaching; attainment was related to the student experience, including student learning attentiveness and participation; a passion for teaching was related to intrinsic value; and time was most associated with the cost value.…”
Section: Decisional Balancementioning
confidence: 99%
“…This perspective is also seen in the decisional balance associated with TTM and the decision to make health behavioral changes. As summarized by Matusovich et al 9 , in a review of literature on Expectancy Value Theory and the adoption of teaching practices, all four categories are observed in faculty decisions regarding instructional approaches 10 . This perspective was also seen in Finelli et al's 11 focus group of faculty: expectancy was clustered around knowledge and skills of effective teaching; attainment was related to the student experience, including student learning attentiveness and participation; a passion for teaching was related to intrinsic value; and time was most associated with the cost value.…”
Section: Decisional Balancementioning
confidence: 99%
“…A number of books 1,2 , research papers 3,4,5,6 , and reports 7,8,9 point out the non-adoption or nontranslation of research-based instructional practices, and the phenomenon is often known as the valley or chasm of death. Research on barriers to change 3,4,10,5,11 has revealed a variety of reasons for the valley of death for educational innovations, and there has been a strong push to investigate solutions to this problem.…”
Section: Importance Of Translational Researchmentioning
confidence: 99%
“…It is clear that factors from each of the three categories influence each other, and in the last few years various reports 13,14 and research studies 5,15,6 have called for changes at the systemic level in higher education, especially in the STEM fields. We welcome these initiatives, and we hope that they bring about systemic changes.…”
Section: Barriers To Research/classroom Transitionsmentioning
confidence: 99%
“…The students who participated in the FIU mentorship program gained valuable insight into engineering as a profession, encouraging them to persist in engineering. Even graduate students benefit from mentoring, demonstrating its value at every stage in a student's career [21] . Most of the major MEOs offer mentorship programs to members at different stages in their academic and professional careers [3,27,35] .…”
Section: Introductionmentioning
confidence: 99%